Income polarization in the People's Republic of China: Trends and changes - Guanghua Wan; Chen Wang (Asian Development Bank Institute (ADBI), 2015)
This paper estimates income polarization in the People'http://www.adb.org/publications/income-polarization-prc-trends-changess Republic of China (PRC) from 1978 to 2010 and decomposes the estimated polarization by population subgroup. In addition, a framework is proposed to disentangle a change in polarization into a growth and a redistribution component. This framework is then used to quantify the contributions of various income sources to a rise in polarization in the PRC between 2002 and 2007. The analytical results suggest that (1) income polarization exhibited a broadly increasing trend from 1978 to 2010; (2) income polarization was large and rising among rural citizens, while low and declining among urban citizens; polarization of migrants also declined; (3) geographically, income polarization rose in east and particularly central PRC, while west PRC was most polarized with little change over time; and (4) the rise in polarization between 2002 and 2007 was mainly driven by the investment income, followed by transfers. Conversely, business income is polarization-reducing, especially in rural PRC. To a lesser extent, wage is also polarization-reducing, especially among migrants.
Keywords: D31; D63; D74; O53; 330